Mesenchymal stem cell transplantation as a potential therapy for refractory lupus nephritis: A systematic review - Faisal Parlindungan; Johanda Damanik; Abirianty P. Araminta; Ariel V. Soetedjo; Rudy Hidayat; Suryo A. Kusumo Wibowo; Anna Arianne; Sumariyono Sumariyono (Rheumatology & Autoimmunity, 2023)
Abstract Background Lupus nephritis (LN) results in high morbidity and mortality in patients with systemic lupus erythematosus. Refractory cases of standard immunosuppressive therapy have been recorded. Mesenchymal stem cell transplantation (MSCT) shows potential use in autoimmune diseases. We aim to review MSCT in the treatment of refractory LN. Methods Published articles were systematically extracted from the databases in May 2022. The quality of the studies was assessed using the Oxford Centre for Evidence‐Based Medicine critical appraisal checklist. Results Four studies were included. All studies recruit severe or refractory LN patients and show significant improvement in post‐MSCT 24‐h proteinuria. However, the improvement of renal function after MSCT is inconsistent between studies after a 1‐month follow‐up, with one study showing deterioration of the estimated glomerular filtration rate after 3 months and one study showing an increase in serum creatinine at 6 and 9 months. Moreover, all studies show improvement in Systemic Lupus Erythematosus Disease Activity Index scores after MSCT, while two studies show that a decrease in anti‐double‐stranded DNA (anti‐dsDNA) levels after MSCT is only evident for up to 1‐month period. Conclusions MSCT can be effective, especially in severe or refractory LN. More randomized‐controlled trials are needed to support this evidence.